Vochysia awasensis (Vochysiaceae), new species from the Mountain Forests from the Ecuatorian Chocó - Huamantupa Chuquimaco, Isau (2011)
Vochysia awasensis I. Huamantupa, is described and illustrated as new species of the family Vochysiaceae, belonging to the sect. Stafleu Ciliantha subsect. Megalanthae Stafleu, which comes from the montane forests of the Choco biogeographical region in the northwestern of Ecuador. The new species differs from its relatives V. megalantha and V. duquei, by its inconspicuous and recurrent petiole, blade 17-33,5 (-35) x 4,5-10 cm, and petals 2,4-3 x 0,6 to 0,9 cm.